Determinants of measles seroprevalence among pregnant women in Paris, France. (7th January 2014) - Bodilis, H.; Goffinet, F.; Krivine, A.; Andrieu, T.; Anselem, O.; Tsatsaris, V.; Rozenberg, F.; Launay, O.; Kaiser, L.
Abstract Non‐immune pregnant women are at risk of severe measles. As the measles vaccination is contraindicated during pregnancy, women should be vaccinated before conception or during the postpartum period. Nevertheless, measles serology is not recommended during pregnancy in France, and there are no data available concerning measles susceptibility and its associated risk factors among pregnant women. The socio‐demographic determinants of measles seronegativity have been identified in a prospective cohort of 826 pregnant women in Paris, France. Measles seronegativity was 10.41% (95% CI 8.32–12.50). Women from higher socio‐economic groups, born in France after 1980, were more frequently seronegative.